The use of protective masks and the level of arterial oxygen saturation at rest and after exercise - Paulina Majek; Angelina Kaleta-Pilarska; Kamil Barański (Medycyna Pracy, 2022)
Background Studies of influenza, and human coronaviruses provide evidence that the use of a medical mask can prevent the spread of infectious droplets from an infected person to someone else. After global public health emergency of coronavirus SARS-CoV-2 causing illness of COVID-19 was changing frequency of wearing a mask. Therefore, study was undertaken to assess whether the use of protective masks affects the level of oxygen saturation during rest and during exercise.